Searching dark-matter halos in the GaBoDS survey - Maturi, Matteo; Meneghetti, Massimo; Bartelmann, Matthias (Arxiv, 2017)
We apply the linear filter for the weak-lensing signal of dark-matter halos developed in Maturi et al. (2005) to the cosmic-shear data extracted from the Garching-Bonn-Deep-Survey (GaBoDS). We wish to search for dark-matter halos through weak-lensing signatures which are significantly above the random and systematic noise level caused by intervening large-scale structures. We employ a linear matched filter which maximises the signal-to-noise ratio by minimising the number of spurious detections caused by the superposition of large-scale structures (LSS). This is achieved by suppressing those spatial frequencies dominated by the LSS contamination. We confirm the improved stability and reliability of the detections achieved with our new filter compared to the commonly-used aperture mass (Schneider, 1996; Schneider et al., 1998) and to the aperture mass based on the shear profile expected for NFW haloes (see e.g. Schirmer et al., 2004; Hennawi & Spergel, 2005). Schirmer et al.~(2006) achieved results comparable to our filter, but probably only because of the low average redshift of the background sources in GaBoDS, which keeps the LSS contamination low. For deeper data, the difference will be more important, as shown by Maturi et al. (2005). We detect fourteen halos on about eighteen square degrees selected from the survey. Five are known clusters, two are associated with over-densities of galaxies visible in the GaBoDS image, and seven have no known optical or X-ray counterparts.